PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP TINGKAT DISIPLIN KERJA GURU - Edi Saputra; Wati Angraini (STKIP Pesisir Selatan, 2026)
Teacher work discipline is one of the important indicators of educator professionalism that directly affects the effectiveness of the learning process. This study aims to determine the effect of principal leadership on the level of teacher work discipline at SDN 107/III Air Mumu, Gunung Raya District, Kerinci City. This research uses a quantitative approach with a survey method. The population of this study were all 11 teachers of SDN 107 / III Air Mumu, and the entire population was used as a research sample. The instrument used is a questionnaire with a five-point Likert scale. Data collection was carried out using a closed five-point Likert scale questionnaire that had been tested for validity and reliability. Data were analyzed using simple linear regression analysis. The results showed that there was a positive and significant influence between principal leadership and teacher work discipline, with a correlation value of r = 0.682 and an influence contribution of 46.5%. This finding indicates that the better the principal's leadership, the higher the level of teacher work discipline. The implication is that principals need to increase the role of transformational leadership and exemplary to foster a culture of discipline in schools.